Escolas de contas e o controle social na formação profissional - Souza, Patrícia Verônica Nunes Carvalho Sobral de (2017)
This Thesis is a knowledge construction and deepening of the theme ''School of Accounts and social control on professional training". The focus is on the Brazilian Schools of Accounts, mainly on the José Amado Nascimento School of Accounts - ECOJAN, of the State of Sergipe's Court of Accounts. The guiding question is: the José Amado Nascimento School of Accounts (ECOJAN) plays the role of arousing society's interest in overseeing the allocation of public resources, by granting to civil servants, people under the jurisdiction and society notions of democracy, citizenship, ethics, transparency and participatory process in the monitoring of public spending and forms of social control? It starts from the premise that information and knowledge are instruments of change regarding the glance upon the social control of public resources. The monitoring and auditing systems of the Courts of Accounts, in integrated action with their schools of accounts, develop projects aimed at their servants and those under the jurisdiction through qualification, improvement and specialization courses on the real needs for the proficient execution of their technical-functional activities, assuming a didactic-pedagogical and propedeutic attitude by means of projects developed inside or outside the respective schools of accounts. Thus, the purpose of this Thesis is to understand the performance of the José Amado Nascimento School of Acounts in promoting the exercise of social control in the State of Sergipe. The methodological procedure was the field study, developed through data gathered from interviews with students and teachers contemplated in "TCE Citizen/SE Project" and with the most recent and oldest schools of accounts in Brazil, as well as from questionnaires answered by directors/coordinators of all brazilian schools of accounts, for the purposes of analyses and systematizations on this entity's performance, within the Sergipe's context, with the aid of technical reports aimed at the measurement of social control promotion. This research is structured as a case study, on a qualitative approach and content analysis, establishing a dialogue between the results to reach an understanding of the historical/constitutional aspects of the courts of accounts, as well as evolutionary/ statistical regarding the brazilian schools of accounts' activities, with specificity for the State of Sergipe's School of Accounts - ECOJAN and its performance for the promotion of educational practices intended stimulate the exercise of social control by civil servants and civil society. Regarding the results, the research showed that the educational practice, designed to the servants and the projects for society, are drivers of social control in terms of public resources fiscalization, by the ECOJAN and some schools of accounts of Brazil. Nevertheless, such practices are still incipient and must be further intensified.